EFFECTS OF HEATING AND SUGAR ON THE QUALITY OF HARD CANDY MADE OF SYRUP KALAMANSI SIDEPRODUCT - Ferdy Saputra Hutagalung; Kurnia Harlina Dewi; Bosman Sidebang (BPFP Faperta UNIB, 2019)
This research aims to get the effect of long warming (minutes) and the type of sugar in the manufacture of calamansi candy which are seen from the physical, chemical and organoleptic test. To get long warming and type of sugar that produces the best calamansi and also to compare the best calamansi with SNI candy and give information about the nutritional values of candy. This research was conducted at the Laboratory of Agricultural and Industrial Technology Laboratory, University of Bengkulu. This research needs 12, 14, and 16 minutes to produce the calamansi candy. The data obtained were analyzed by using variety of two directions ANOVA method for (moisture content, ash content and pH), the data obtained for organoleptic test by using of one direction ANOVA method . The result is different and did TREN test (TUKEY) and the result of peroksimat analysis data that obtained should compared with SNI Candy (3547.1: 2008). The result of the research showed that the most preferred of calamansi candy consumers was granulated sugar with a long warming by 14 minutes and for liquid sugar of calamansi candy favored of consumers was melted sugar with a long warming by 16 minutes, judging of the physical characteristic of (moisture content) and chemical characteristic of (pH and ash content) had fulfill SNI candy. To know the nutritional values of calamansi candy so have to do the proximate analysis (reduction of sugar, protein, total acid, carbohidrat and vitamin C). Diversification of product calamansi candy has qualified to be developed into a business calamansi agro industry in Bengkulu but, after further the research concerning the economic feasibility as well as shelf life of calamansi candy.